Comparison of serum acetyl hydrolase (PAF-AH) and paraoxonase 1 (PON1) values between prostate cancer patients and a control group - Erdal Benli (Kaohsiung Journal of Medical Sciences, 2017)
The aim of the study was to measure platelet-activating factor acetyl hydrolase (PAF-AH) and paraoxonase (PON1) enzyme activity levels in patients with high Psa values to compare with healthy peers and also to determine the efficacy of these parameters in predicting pathologic results of patients with high Psa values. This study included 66 patients with Psa value > 4 ng/dl (Group 1) and 44 patients with Psa <4 ng/dl (Group 2) for a total of 110 patients. Parameters measured in serum of PON1, PAF-AH, and MDA were compared between the groups. Additionally the same parameters were compared between patients with prostate biopsy performed due to high Psa and diagnosed with cancer and the control group with normal Psa values. The PAF-AH activity in Group 1 was 125.17 ± 8.64 and in Group 2 was 120.08 ± 9.23 U/ml (p = 0.003). The PON1 activity was 63.12 ± 6.74 and 65.91 ± 7.77 U/ml in the groups, respectively (p = 0.04). Additionally, there were significant differences identified between the control group and PCa diagnosis group in terms of PAF-AH and PON1 activities (p = 0.004 and p = 0.02, respectively). The enzyme activity of PAF-AH and PON1 measured in serum of patients with high Psa value and patients with diagnosis of prostate cancer (PCa) were identified to have changed by a significant amount compared to healthy peers with normal Psa value. It was concluded that these parameters may be beneficial markers for use in assessment of patients with high Psa value.